2016
DOI: 10.1080/0267257x.2015.1129985
|View full text |Cite
|
Sign up to set email alerts
|

The baby boomer market maven in the United Kingdom: an experienced diffuser of marketplace information

Abstract: This study identifies and profiles market mavens among the baby boomer generation in the United Kingdom. Boomers are an important market segment, yet most advertising targets younger audiences, making word-of-mouth communications crucial among this older cohort. Findings suggest boomer mavens place great importance on 'respect' values, are particularly concerned with fashion and compared with non-mavens are more likely to try new brands, watch more television, hold positive attitudes towards advertising and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…Likewise, recent studies point out that market mavens do not connect in the marketplace presently to articulate altruism but in addition to personal motives, to enhance self-esteem, to establish high self-efficacy, to enhance confidence, require distinctiveness, perfectionism, and materialism. Besides, in [122] the authors emphasize that market mavens have positive attitudes towards advertising, which they believe to be a consistent medium of information and source of consumer knowledge and information. The authors of [123] have demonstrated that perceived high flow practice, immersive and pragmatic satisfaction are the key elements of market mavens in the virtual environment.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, recent studies point out that market mavens do not connect in the marketplace presently to articulate altruism but in addition to personal motives, to enhance self-esteem, to establish high self-efficacy, to enhance confidence, require distinctiveness, perfectionism, and materialism. Besides, in [122] the authors emphasize that market mavens have positive attitudes towards advertising, which they believe to be a consistent medium of information and source of consumer knowledge and information. The authors of [123] have demonstrated that perceived high flow practice, immersive and pragmatic satisfaction are the key elements of market mavens in the virtual environment.…”
Section: Discussionmentioning
confidence: 96%
“…Individuals high on this behaviour are market mavens who position themselves as purveyors of market information (Feick & Price, 1987). Market mavens tend to be highly engaged with the market and seek to acquire and share knowledge about same to project an 'expert' image of themselves (Packard & Wooten, 2013;Sudbury-Riley, 2016). This positions mavenism as a form of engagement behaviour given that it can be directed at a particular brand (Feick & Price, 1987).…”
Section: Susceptibility To Influencementioning
confidence: 99%
“…This positions mavenism as a form of engagement behaviour given that it can be directed at a particular brand (Feick & Price, 1987). Because mavens want to be seen to be aware of changes in the market (Lee, Leizerovici & Zhang, 2015), they may participate in online activations as a means of showing that they are 'on top of' happenings in the market (Sudbury-Riley, 2016).…”
Section: Susceptibility To Influencementioning
confidence: 99%
“…Second, previous studies have mainly taken a dichotomous approach to unique consumers (i.e., opinion leaders or non-leaders, or mavens or non-mavens), lacking further segmentation and consumer profiles [1,13,14,34]. Market segmentation keeps businesses closely in touch with their consumers, ensures more efficient resource allocation, and results in marketing programs attuned to consumer needs [35] and a competitive advantage within the segment [36].…”
Section: Introductionmentioning
confidence: 99%